Analisis Hidrologi dan Hidrolika pada Saluran Drainase Ramanuju Hilir Kotabumi (Menggunakan Program HEC-RAS) - Mustofa, Muhammad Jazuli; Kusumaastuti, Dyah Indriana; Romdania, Yuda (Universitas Lampung, 2015)
The calculation is done using the rainfall data obtained from BMKG Kotabumi North Lampung,from 1998 until 2011 with time increment in minutes. The Log Pearson III method is used to findthe design rainfall with return period 2 years, 5 years and 10 years. Then the result isimplemented in the Intensity-duration-frequency (IDF) curves. Time of concentration is linked intothe IDF curves to determine rainfall intensity. Based on the calculated rainfall intensity, thedesign discharge for each return period can be calculated using the rational method.The values of design discharge are then inputted as upstream boundary condition in HEC-RAS.Model output are presented in cross and long section to determine at which return period thedrainage capacity is overflowed. Simulation using HEC-RAS were also done to determine thechannel capacity.Based on the results of this research, it can be concluded that rainfall intensities are 52,6918mm/hour, 65,7820 mm/hour and 75,9032 mm/hour, for 2, 5, an 10 year return period respectively.The capacity of the drainage channel is 2.02 m 3 /hour and is expected to be exceeded on 5 yearsreturn period.Key words : Intensity, Rasioanal method, HEC-RAS, capacity